The Crucial Role of Turnover Intentions in Transforming Moral Disengagement Into Deviant Behavior at Work - Christian, Jessica Siegel; Ellis, Aleksander P. J. (2014)
Organizational deviance represents a costly behavior to many organizations. While some precursors to deviance have been identified, we hope to add to our predictive capabilities. Utilizing social cognitive theory and psychological contract theory as explanatory concepts, we explore the role of moral disengagement and turnover intentions, testing our hypotheses using two samples: a sample of 44 nurses from a hospital system in the Southwestern United States (Study 1), and a sample of 52 working adults collected from an online survey system (Study 2). Results strongly supported our hypotheses in both samples, indicating that the self-regulatory deactivation inherent in moral disengagement led to increased organizational deviance; effects that were much more pronounced when turnover intentions were high. Our findings support the increased role of cognition in determining behavior when environmental pressures stemming from the psychological contract have been altered, leading to a number of theoretical and practical implications, particularly in industries with high turnover rates.
Keywords: Turnover intentions; Social cognitive theory; Psychological contract theory; Moral Disengagement; Deviant Behavior